2022
DOI: 10.3389/fonc.2022.903706
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Radiation Dose Measurements in a Scanning Proton Therapy Room: Can Parents Remain Near Their Children During Treatment?

Abstract: PurposeThis study aims to characterize the neutron radiation field inside a scanning proton therapy treatment room including the impact of different pediatric patient sizes.Materials and MethodsWorking Group 9 of the European Radiation Dosimetry Group (EURADOS) has performed a comprehensive measurement campaign to measure neutron ambient dose equivalent, H*(10), at eight different positions around 1-, 5-, and 10-year-old pediatric anthropomorphic phantoms irradiated with a simulated brain tumor treatment. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
1
7
0
1
Order By: Relevance
“…Overall trends obtained for the secondary neutrons generated by primary oxygen beams, both for the pristine Bragg peaks and the SOBPs, are in agreement with the previous study using primary protons, helium and carbon ions (Vedelago et al 2022). The secondary neutrons spectra follow the typical shape of energy distributions of secondary neutrons encountered in ion beam therapy, with one peak in the TE region and another peak in the FR region, with a flat thermalization region in between (Mares et al 2022, Shrestha et al 2022. In the obtained spectra, the evaporation peak is usually eclipsed by the cascade peak, as no additional room elements or room walls were considered (Englbrecht et al 2021).…”
Section: Energy Distribution Of the Secondary Neutronssupporting
confidence: 88%
“…Overall trends obtained for the secondary neutrons generated by primary oxygen beams, both for the pristine Bragg peaks and the SOBPs, are in agreement with the previous study using primary protons, helium and carbon ions (Vedelago et al 2022). The secondary neutrons spectra follow the typical shape of energy distributions of secondary neutrons encountered in ion beam therapy, with one peak in the TE region and another peak in the FR region, with a flat thermalization region in between (Mares et al 2022, Shrestha et al 2022. In the obtained spectra, the evaporation peak is usually eclipsed by the cascade peak, as no additional room elements or room walls were considered (Englbrecht et al 2021).…”
Section: Energy Distribution Of the Secondary Neutronssupporting
confidence: 88%
“…Neutrons created during proton‐RT have a wide range of energies, ranging from thermal energies (<0.4 eV) up to the maximum proton energy (up to 250 MeV) 9,10 . As neutrons are indirectly ionizing, they will deposit energy by creating ionizing secondary particles.…”
Section: Out‐of‐field Dosimetry During Proton‐rtmentioning
confidence: 99%
“…Neutrons created during proton‐RT have a wide range of energies, ranging from thermal energies (<0.4 eV) up to the maximum proton energy (up to 250 MeV). 9 , 10 As neutrons are indirectly ionizing, they will deposit energy by creating ionizing secondary particles. These nuclear reaction cross‐sections strongly depend on the neutron energy, causing the relative biological effectiveness (RBE) of neutrons to vary greatly for different neutron energies.…”
Section: Out‐of‐field Dosimetry During Proton‐rtmentioning
confidence: 99%
“…In the absence of robust shielding, these radiation fields could potentially present significant risks, not only to the healthcare professionals but also to the general public. It is worth noting that the effect of the secondary neutron field has been studied in the following studies: Agosteo et al (1998), Hälg and Schneider (2020), and Mares et al 2022. Agosteo et al reported that the estimated secondary gamma-ray dose was approximately one-tenth of the combined total dose from neutrons and gamma rays.…”
Section: Introductionmentioning
confidence: 99%